Terahertz Imaging and Machine Learning in the Classification of Coffee Beans - Uceda P. (2021)
Acknowledgments. P. Uceda and H. Yoshida acknowledge the financial support from Project Concytec – The World Bank “Mejoramiento y Ampliación de los Servicios del Sistema Nacional de Ciencia Tecnología e Innovación Tecnológica” 8682-PE through Fondecyt [contract no 006–2018].